INCOME ISLAMIC SHARIA ECONOMIC VALUE IN KSPPS MITRA ANDA SEJAHTERA SEMARANG PRODUCTS FOCUSES ON MUDHARABAH, MUDHARABAH AND MUSYARAKAH DEPOSITS - Edy Faozaeni; Nafis Irkhami (SEAN Institute, 2023)
This study aims to determine the application of Islamic Economic Value to Mudharabah, Mudharabah and Musyarakah deposits, namely at KSPPS Mitra Anda Sejahtera. This type of research is qualitative research and data collection techniques by conducting observations, interviews and documentation, with researchers conducting data analysis, presenting data and drawing conclusions. The results of this study indicate that there is a discrepancy with the principles of Islamic Economic Value (Syar'iah) in the implementation of financing products in the form of Depisito Mudharabah, Mudharabah and Musyarakah products at KSPPS Mitra Anda Sejahtera.